Performance Evaluation of Machine Learning Classifiers for Epileptic Seizure Detection - Farahi, Mirwais; Doreswamy (International Journal of Computer Sciences and Engineering, 2019)
Epilepsy is a neurological disorder in the human brain, which is characterized by chronic disorders and occurs at random to interrupt the normal function of the brain. The diagnosis and analysis of epileptic seizure is made with the help of Electroencephalography (EEG). In order to detect seizure, this study aims to construct an automatic seizure detection system to analyze epileptic EEG signals. The CHB-MIT Scalp EEG dataset is used for the experiment purpose. The Welch Fast Fourier Transform is applied to convert time-domain signals to frequency-domain. The statistical features are extracted from both time and frequency domains. The ANOVA based feature selection is used to select the most significant features. Data under-sampling and over-sampling techniques are used to balance the data. Eight machine learning algorithms, including Decision Tree, Extremely Randomized Decision Tree, Linear Discriminant Analysis, Quadratic Discriminant Analysis, Random Forest, Gradient Boosting, Multilayer Perceptron, and Stochastic Gradient Descent are used to classify the data. The highest result is recorded as 99.48% of accuracy, 99.79% of sensitivity, and 99.17% of specificity for the Extremely Randomized Decision Tree. The system might be a helpful tool for physicians to make a more reliable and objective analysis of a patient`s EEG records.